Influence of support on catalytic behavior of nickel catalysts in the steam reforming of ethanol for hydrogen production - Fajardo, Humberto V.; Longo, Elson [UNESP]; Mezalira, Daniela Z.; Nuernberg, Giselle B.; Almerindo, Gizelle I.; Collasiol, Andre; Probst, Luiz F. D.; Garcia, Irene T. S.; Carreno, Neftali L. V. (Springer Heidelberg, 2010)
Al(2)O(3), MgO, SiO(2) and ZnO-supported nickel catalysts were prepared and evaluated in the ethanol steam reforming for hydrogen production. It is shown that the catalytic behavior can be influenced depending on the experimental conditions employed and chemical composition of the catalyst.
Keywords: Steam reforming; Ethanol; Hydrogen; Nickel catalysts